(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the effect of casein supplementation on the periodontium and mandibular bone of rats fed a standard diet and a cafeteria diet. Methodology: 24 Wistar rats were divided into four experimental groups: normal diet (DN), normal diet with casein (DNC), cafeteria diet (DC) and cafeteria diet with casein (DCC). The DNC and DCC groups received 2 mL of micellar casein from the 60th to the 90th day. At 90 days, the animals were orthouthanized and the materials were collected for analysis. Results: The animals in the DC and DCC groups showed a higher adiposity index compared to DN and DNC (p <0001). The DCC group had a significantly lower HDL cholesterol level than DN (p <0.0092). In the radiographic analysis of the animals’ hemimandibula, no difference was observed in relation to pixel density, however, there was a difference in the size of the anterior mandibular portion between DCC and DNC (p <0.0196) and DCC and DN (p <0.0039). Histologically, there was a reduction in blood vessels, both in alveolar bone (p = 0.0033), furcation bone (p <0.0001) and periodontal ligament (p = 0.0001) in CHD. In addition, in the alveolar bone there was a decrease in osteocytes in the DCC group in relation to the CND (p = 0.0198). Conclusions: The increase in adiposity contributed to the decrease of blood vessels and osteocytes in the bone tissue of rats, despite not influencing inflammation. This effect was independent of casein. Therefore, casein supplementation in rats submitted to a cafeteria diet was not effective in decreasing the accumulation of adipose tissue, as well as not positively interfering in the bone metabolism of the hemimandibula.